NASA - Hakkila, Jon and Adele D. Richardson (Mankato, MN Smart Apple Media, 2000)
Examines the functions of NASA and the impact of its various space exploration programs.
Keywords: United States; National Aeronautics and Space Administration; Series: Above and Beyond